2013
DOI: 10.5772/50644
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Humanoid Robots for Theatrical Performances

Abstract: The purpose of this research is to develop multitalented humanoid robots, based on technologies featuring high-computing and control abilities, to perform onstage. It has been a worldwide trend in the last decade to apply robot technologies in theatrical performance. The more robot performers resemble human beings, the easier it becomes for the emotions of audiences to be bonded with robotic performances. Although all kinds of robots can be theatrical performers based on programs, humanoid robots are more adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, this study is the first one to quantify the facial correlates of character portrayal separate from emotions associated with characters. While a small number of studies have examined characters as vehicles for expression—for example, using cartoon characters ( Liu, Chen, & Chang, 2019 ; Zhao, Meng, An, & Wang, 2019 ), virtual models ( Hahn, Castillo, & Cunningham, 2019 ), avatars ( Ennis, Hoyet, Egges, & McDonnell, 2013 ; Tinwell, Grimshaw, Nabi, & Williams, 2011 ; Wallraven, Bülthoff, Cunningham, Fischer, & Bartz, 2007 ), and robots ( Lin et al, 2013 )—the tasks analysed in these studies have been firmly rooted in measurements of emotion, rather than the characters themselves.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this study is the first one to quantify the facial correlates of character portrayal separate from emotions associated with characters. While a small number of studies have examined characters as vehicles for expression—for example, using cartoon characters ( Liu, Chen, & Chang, 2019 ; Zhao, Meng, An, & Wang, 2019 ), virtual models ( Hahn, Castillo, & Cunningham, 2019 ), avatars ( Ennis, Hoyet, Egges, & McDonnell, 2013 ; Tinwell, Grimshaw, Nabi, & Williams, 2011 ; Wallraven, Bülthoff, Cunningham, Fischer, & Bartz, 2007 ), and robots ( Lin et al, 2013 )—the tasks analysed in these studies have been firmly rooted in measurements of emotion, rather than the characters themselves.…”
Section: Introductionmentioning
confidence: 99%
“…While robots are increasingly performing character versions of themselves, there are many open-ended questions and limitations to consider [35]. In 2009, Lin et al reported on the realization of one of the earliest robot theater performances with a cast of two biped androids and two twin-wheeled two-armed humanoid robots [36]. The following adaptations of literary works-where NAO assumes the lead role-constitute our modest contribution to this interesting field.…”
Section: Theatrical Performancesmentioning
confidence: 99%
“…The play took place in 2011, with public audience and it was 18 minutes long. Fahn and collaborators [6], [15] believe that humanoid robots are more suitable as theatre actors than other kind of robots. Their robots are capable to perform autonomously many actions as: draw people, jazz drumming, marionette operating, notation reading, and singing.…”
Section: B No Audience Interactionmentioning
confidence: 99%
“…Theatre has been suggested as a suitable environment [1], [5]- [8] to test timing and expressiveness. Despite this, just few works have been developed using theatre as environment [6], [9]- [18]. Yet, these works have focused on the use of theatre as space to build entertainment robots without implementing autonomous abilities to show emotion or social behavior.…”
Section: Introductionmentioning
confidence: 99%